Sleeping patterns among preschool children and related challenges and strategies in an urban home setting - Ceralde, January A. (College of Home Economics, University of the Philippines Diliman, 2019)
This study aimed to describe the sleeping patterns, determine related challenges and strategies, and identify the determinants that may be associated among preschool children (3-5 years old) in an urban home setting. One hundred twenty parents from three preschools in Quezon City answered the survey questionnaire. From the survey questionnaire participants, thirty (30) parents or primary caregivers were chosen for an interview. The study has shown that around 10:00 pm is the most common sleeping time of preschool children for both weekdays and weekends. Moreover, the common wake up time are around 7:00 am and 10:00 am on weekdays and weekends, respectively. Study shows that preschool children who were male, first born, without siblings, and in the afternoon classes have higher possibility of having a regular sleep. Whereas, parents who were employed and full-time at work have higher possibility that their children will obtain irregular sleep. The study identified key determinants that associated with children's sleep are the age, presence of a sibling, school schedule, employment status and type of work. Doing homework, playing toys, and drinking milk were common activities before bedtime. Furthermore, afraid of sleeping alone is the most common sleeping problem among preschoolers. Having knowledge about improving sleep and its strategies are strongly influenced by the family and peers in the Microsystem level of Urie Bronfenbrenner. Inadequate sleep and sleep challenges among preschool children can have effects on both the child and the parent or primary caregiver's daily activities.